CORPORATE CRIMINAL LIABILITY IN INDONESIA ON THE PERSPECTIVE OF COMPARISON - Chasani, Muchammad (IJCLS (Indonesian Journal of Criminal Law Studies), 2017)
The regulation of corporate criminal liability in Indonesia's criminal justice system is basically a new and still debatable issue. It is said that because in the Criminal Code is not recognized and regulated explicitly about the corporation as a subject of criminal law. This is a natural thing since the WvS Criminal Code still adheres to the principle of "societas delinquere non potest" or "non-potest university delinquere", that is, a legal entity can not commit a crime. Thus, if in a society there is a criminal offense, then the criminal act is deemed to be done by the board of the corporation concerned. Regarding the corporate criminal responsibility system in Indonesia, in the corruption law Article 20 paragraph (1), if the corporation committed a criminal act of corruption, then those responsible for the criminal act shall be the corporation only, the management only, or the corporation and its management. Thus, it can be said that the regulation of corporate criminal liability in the legal system in Indonesia is expressly only regulated in special criminal legislation, because the Criminal Code of WvS still adheres to the principle of "societas delinquere nonpotest" so it is not possible to enforce corporate criminal liability in it.